Pengaruh Belanja Langsung, Belanja Tidak Langsung dan Kualitas Sumber Daya Manusia Terhadap Pertumbuhan Ekonomi Kabupaten/Kota Di Kalimantan Barat Periode 2008 - 2012 - B01110012, ANSORI (Jurnal Curvanomic, 2016)
This study entitled "the influence of expenditure direct and indirect and the quality of humanresources on economic growth districts in west Kalimantan", Which aims to examine and analyze thegovernment spending the direct spending, indirect, and the quality of human resources against; withrespect to economic growth west Kalimantan years 2008-2012".The analysis used is regression analysis data panels in use to see the relationship betweenvariable government spending the field of direct expenditure, indirect, and the quality of humanresources on economic growth districts in west Kalimantan province. The data used was secondarydata years 2008-2012 consisting of 14 districts in west Kalimantan province from statistics Indonesia(bps) and the ministry of finance.The result of the research indicated that direct expenditure and expenditure indirect haveleverage a significant impact on economic growth, while the quality of human resources have aninsignificant on economic growth. This means economic growth influenced together by governmentspending the field of direct expenditure and expenditure indirect.